The Influence of the Cooperative Script Type Cooperative Learning Model in Economics Learning on Student Learning Outcomes at SMA Negeri 1 Bangkinang City - Zahwa Sekar Fadhilah; Sri Arita (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2026)
Objective: Objective: This study aimed to analyze the effect of the Cooperative Script learning model on the Economics learning outcomes of tenth-grade students at SMA Negeri 1 Bangkinang City. Method: The research employed a quantitative approach with a pre-experimental design using a Pretest–Posttest Control Group Design. The sample consisted of experimental and control classes selected from grade X students. Data were collected through pretest and posttest instruments and analyzed using normality, homogeneity, and hypothesis testing. Results: The findings showed that the implementation of the Cooperative Script learning model had a positive and significant effect on students’ Economics learning outcomes. Students in the experimental class demonstrated higher posttest scores compared to the control class taught through conventional lecture methods. The prerequisite tests indicated that the data were normally distributed and homogeneous, confirming the validity of the statistical analysis. The effect size analysis also revealed that the Cooperative Script model provided a moderate to strong contribution to improving student learning achievement. Novelty: This study contributes to the development of cooperative learning research by providing empirical evidence on the effectiveness of the Cooperative Script model in improving Economics learning outcomes at the senior high school level, particularly within the context of Indonesian secondary education, where studies focusing specifically on Economics subjects are still limited.